Strategi Komunikasi Dakwah dalam Mengubah Tradisi Negatif Baronggeng pada Walimatul Urs - Ismiati, Ismiati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to find out the form of the Baronggeng tradition in Walimatul Urs and how the da'i's preaching communication strategy is in resolving the problem of the meaning of the Baronggeng Tradition in Walimatul Urs. This research uses qualitative methods, descriptive analysis techniques, and ethnographic approaches. Descriptive analysis techniques provide a detailed description of a phenomenon that occurs. This research data was obtained from the observation and interview and analyzed using data reduction techniques, data presentation, and conclusions. This research shows that the Baronggeng tradition in Walimatul Urs in Sidangoli Gam Village, North Maluku, has mixed with the outside. The traditional form of tradition, originally packaged traditionally after cultural mixing, has changed to become more modern but tends to invite negative things and is contrary to Islamic teachings. Meanwhile, the da'wah communication strategy implemented in the context of training is carried out through the role of tackle councils, education in schools, and interpersonal da'wah among traditional practitioners.